Impact of integrity and internal audit transparency on audit quality: the moderating role of blockchain / Mohammad Rokibul Kabir ...[et al.] - Kabir, Mohammad Rokibul; A. Sobhani, Farid; Mohamed, Norhayati; Ashrafi, Mehrab (Universiti Teknologi MARA, 2022)
In today’s corporate environment, the success of external auditors for producing quality reports depends on internal audit functions. Hence, ensuring internal audit quality is a must. Auditors’ integrity and the presence of a transparent internal auditing process may all help to ensure internal audit quality. In this regard, with its irreversible nature, evolving blockchain technology (BT) is playing a critical role in offering a triple entry accounting system. Thus, the purpose of this article is to describe how integrity (INTI) and internal audit transparency (TRPY) affect internal audit quality (AQLY). It also assesses the potential of blockchain technology as a moderating function in influencing AQLY. The Partial Least Square Structural Equation Model (PLS-SEM) was used to describe the causal connection in this research. A self-administrated questionnaire was used to obtain primary data from Bangladeshi accounts and audit practitioners. According to the results, integrity and internal audit transparency substantially influence AQLY. The potential application of blockchain (APBN) has been discovered to moderate the relation between INTI and AQLY. TRPY and AQLY have a similar relationship, which APBN moderates. Thus, this research established a unique model employing INTI, TRPY, and APBN as the determinants, which provided a novel outlook in explaining the factors that can help in improving audit quality.